DIGITAL OILFIELD PERSONNEL DEVELOPMENT MANAGEMENT - Stankovska I. М.; Kochkodan , V.B.; Yanton-Drozdovska , E. (The actual problems of regional economy development, 2021)
The article is aimed at studying the problems associated with the digital oilfield personnel development. The purpose of the article is to study the digital oilfield personnel development management. During the research we used the methods of theoretical generalization - to form definitions of concepts and general approaches and principles; of analysis and synthesis; of system and complex analysis, modeling - for management model formation of digital oilfield personnel development. To achieve this goal, the directions of oil and gas field digitalization are considered; the production process problems faced by managerial and engineering personnel are surveyed. It is shown that for the effective functioning of digital oilfield the highly qualified personnel with the appropriate level of knowledge and experience is needed. The components that should be managed by the organization for staff development and its effective use are identified. The scientific novelty of the study is to solve problems that have theoretical and practical significance in the field of digital oilfield personnel development management. To achieve this goal, the following tasks were solved: - the components of digital oilfield are determined; - the problems that arise during the oil and gas field management are identified; - the concept of personnel development management is defined in order to justify further actions related to the choice of appropriate areas, methods, technologies and forms of training; - the model of digital oilfield personnel development management is formed and its components are analyzed; - the characteristic features of staff development in the mechanistic model of enterprise management are highlighted; - the motivators of professional development of employees are determined, in particular, for advanced training of oil and gas enterprises’ employees resulting in the international IWCF certificate acquisition; - the competence and meta-competence approach of personnel development is analyzed, which should be used to improve the enterprise’s activity.